Corporate Social Responsibility and Cost of Equity Capital : A European Perspective - Sebastian, Kevin Anthone (2013)
This paper examines the effect of Corporate Social Responsibility (CSR) on the cost of equity capital (COE) for a sample of companies in the European continent. Contrary to expectation, the initial finding suggests that CSR has a positive relationship with COE. However, a more in-depth analysis reveals that for companies with above average financial performance, there is a negative relationship between CSR and COE. However, in the case of companies with below average financial performance, the study did not find any significant relationship between CSR and COE. The results also show that participation in manufacturing industry, retail trade industry and transportation, communication and electric services industry by the companies with above average financial performance results in a lower COE. On the other hand, participation in mining industry, which has a negative impact on the environment, results in a higher COE. These results are specific for the companies in the European region for the period 2005 to 2010, a period which was tainted with economic recession.